Optimal design and test of the flexible clamping device for safflower - Yang, Shuangping; Zhang, Zhenguo; Guo, Gang; Zhang, Yi; Qiu, Shilong; Ye, Yunxia (International Journal of Agricultural and Biological Engineering, 2025)
Aiming to address the issues of inconvenience and low efficiency associated with manual harvesting of safflower silk and the high damage rate of cutting harvesting machinery, the effect of manual grasping and drawing was simulated and a safflower drawing and harvesting device was designed based on flexible clamping. A quadratic regression orthogonal rotation combination design was implemented, adopting clamping frequency, spring installation angle, and flower board angle as factors while targeting removal and damage rates as performance metrics. Analysis identified clamping frequency as the predominant factor governing device recovery rate, with spring installation angle and flower board angle exerting secondary influence. Spring installation angle emerged as the dominant factor affecting device damage rate, followed sequentially by flower board angle and clamping frequency. The optimal parameters of the harvesting device are as follows: clamping frequency of 50 times/min, initial installation angle of the spring of 3.2°, and an initial angle of the flower board of 25°. Field tests with optimized parameters demonstrated a 96.28% removal rate and a 2.29% damage rate. The research findings can provide theoretical guidance for the structural design and optimization of the mechanized harvesting device for safflower filaments. Keywords: agricultural engineering, safflower, harvest, clamping, test DOI: 10.25165/j.ijabe.20251803.8536 Citation: Yang S P, Zhang Z G, Guo G, Zhang Y, Qiu S L, Ye Y X. Optimal design and test of the flexible clamping device for safflower. Int J Agric & Biol Eng, 2025; 18(3): 19–24.